Molecular characterization of Indonesia avian influenza virus - N.L.P.I. Dharmayanti; R Damayanti; R Indriani; A Wiyono; R.M.A. Adjid (Indonesian Center for Animal Research and Development (ICARD), 2005)
Avian influenza outbreaks in poultry have been reported in Java island since August 2003. A total of 14 isolates of avian influenza virus has been isolated from October 2003 to October 2004. The viruses have been identified as HPAI H5N1 subtype. All of them were characterized further at genetic level and also for their pathogenicity. Phylogenetic analysis showed all of the avian influenza virus isolates were closely related to avian influenza virus from China (A/Duck/China/E319-2/03(H5N1). Molecular basis of pathogenicity in HA cleavage site indicated that the isolates of avian influenza virus have multiple basic amino acid (B-X-B-R) indicating that all of the isolates representing virulent avian influenza virus (highly pathogenic avian influenza virus). Key Words: Avian Influenza Virus, Molecular Characterization, Poultry, Indonesia